Proceedings of the 11th International Conference on Evaluation of Novel Software Approaches to Software Engineering 2016
DOI: 10.5220/0005913802470253
|View full text |Cite
|
Sign up to set email alerts
|

Developing Green and Sustainable Software using Agile Methods in Global Software Development: Risk Factors for Vendors

Abstract: Global software development (GSD) is gaining momentum due to the potential benefits it offers. GSD aims at delivering remarkable software through a widely distributed pool of experts, with reduced efforts, minimum cost and time. In recent years, GSD developers have reshaped the development processes and have adopted agile techniques and green engineering principles to cope with the frequent changes in requirements, accelerate the development in short increments and to produce energy efficient and sustainable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Apart from the aforementioned online groups, we requested some relevant experts, during the meeting at the “11th International Conference on Evaluation of Novel Approaches to Software Engineering (ENASE 2016), held at Rome, Italy.” During the conference, we received 9 filled questionnaires from relevant experts. Hence, the total questionnaires received were 106 in number.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the aforementioned online groups, we requested some relevant experts, during the meeting at the “11th International Conference on Evaluation of Novel Approaches to Software Engineering (ENASE 2016), held at Rome, Italy.” During the conference, we received 9 filled questionnaires from relevant experts. Hence, the total questionnaires received were 106 in number.…”
Section: Methodsmentioning
confidence: 99%
“…These experts participated from 25 different countries (Asia, 36; Europe, 32; North America, 20; and other, 9). 89 During the conference, we received 9 filled questionnaires from relevant experts. Hence, the total questionnaires received were 106 in number.…”
Section: Questionnaire Distributionmentioning
confidence: 99%
“…Apart from the aforementioned online groups, we requested some of the relevant experts during the meeting at the 11th International Conference on Evaluation of Novel Approaches to Software Engineering (ENASE 2016), held at Rome, Italy . During the conference, we received 9 filled questionnaires from the relevant experts belonging to different countries.…”
Section: Methodsmentioning
confidence: 99%
“…Shukla 3 proposes organizational practices for improved flexibility in different maturity levels of software development. Rashid and Khan 4 emphasized the development of Green and Sustainable Software in the Agile process while surveying the existing methodologies of Software Engineering. Al‐Zewairi et al 5 surveyed the agile methodologies that were proposed from 2002 to 2015 and categorized them into various classes where they found that “Hybrid Agile Methods” are proposed mostly for frequent versioning purposes.…”
Section: Related Workmentioning
confidence: 99%
“…There are many studies 2–9 that evaluate process models using real‐world case studies. However, we found that no study considered using software history to determine software methodological practices such as software release patterns but rather interviewed or surveyed interested stakeholders from a particular development team.…”
Section: Introductionmentioning
confidence: 99%